Overview of Macronutrient Consumption Levels Among Pregnant Women in The Jenangan Subdistrict of Ponorogo Regency - Hanifah, Rofi’atul; Budihastuti, Uki Retno; Lestari, Anik (Nusantara Science and Technology Proceedings, 2024)
Pregnancy demands increased energy and nutrients to support the growing fetus, making proper nutrition crucial for maternal and fetal health. Macronutrients like protein, fat, and carbohydrates are particularly important for providing energy and aiding in cell growth and development. This study seeks to understand how pregnant women in the Jenangan Subdistrict of Ponorogo Regency, Indonesia, consume macronutrients. A descriptive study in January 2024 in Jenangan Subdistrict, Ponorogo Regency, was conducted with 40 participants. Using a 24-hour food recall questionnaire, the data were collected through two interviews with pregnant women by enumerators trained in Nutrition with a D3 degree. This approach aimed to ensure accurate data collection and minimize recall bias. Based on the analysis, macronutrient intake levels varies among participants. Approximately 22,5% had adequate protein intake, with 37,5% showing moderate intake, 20%% report in poor intake, and 20% had deficient intake. For fat consumption, 40% met recommended levels, 27,5% had moderate intake, 15% had poor intake, and 17,5 had deficient intake. Notably, carbohydrate intake was deficient in 97.5% of cases. The research results reveal that pregnant women in the Jenangan Subdistrict, Ponorogo Regency have moderate protein and fat intake levels, but are significantly lacking in carbohydrates. This underscores the importance of targeted nutritional interventions to improve maternal and fetal health in this population.